After you've gone - Lent, Jeffrey (Atlantic Monthly, 2009)
"Henry Dorn has spent years building a family, but it only takes a single afternoon for it to fall apart. Abruptly widowed of the love of his life, Henry buys a steamer ticket for Amsterdam, the city of his heritage, hoping to start life anew. Nothing could have prepared him for the young woman he mets on the ship: the fiery, self- sufficient Lydia Pearce, one of a new generation of women..."--dust jacket.